2015
DOI: 10.1017/s0007114515004560
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of changes in vitamin D status postpartum in Swedish women

Abstract: Low vitamin D status has been associated with unfavourable health outcomes. Postpartum, it is speculated that maternal vitamin D status decreases due to transfer of vitamin D from mother to child through breast milk. A few studies have investigated changes in maternal vitamin D postpartum and possible determinants. Thus, the aims of the present study were to determine changes in serum concentrations of 25-hydroxyvitamin D (25(OH)D) between 2 weeks and 12 months postpartum in Swedish women and to evaluate lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 28 publications
2
16
4
Order By: Relevance
“…Recent studies of breastfeeding women in other countries have also shown a high prevalence of inadequate vitamin D status [18, 20, 21]; however, the prevalence was often lower than those rates found in our study [17, 22]. For example, in Sweden, the prevalence of 25(OH)D concentrations < 50 nmol/L in women, who were breastfeeding for 12 months, was 22% in the winter months (November to April) and 15% in the summer months [17].…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Recent studies of breastfeeding women in other countries have also shown a high prevalence of inadequate vitamin D status [18, 20, 21]; however, the prevalence was often lower than those rates found in our study [17, 22]. For example, in Sweden, the prevalence of 25(OH)D concentrations < 50 nmol/L in women, who were breastfeeding for 12 months, was 22% in the winter months (November to April) and 15% in the summer months [17].…”
Section: Discussioncontrasting
confidence: 90%
“…In our study, the 25(OH)D level was independent of the duration of breastfeeding, and inconsistent results have been reported in previous studies [17, 32, 40]. The duration of breastfeeding may impact vitamin D status in circumstances of an extended breastfeeding duration (>9 months) [40] and in combination with exclusive breastfeeding [32].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Vitamin D deficiency was observed in 30% at baseline, which is comparable to results from recent Danish studies . Vitamin D levels increased during pregnancy, as shown by others . The physiological increase in vitamin D may be due to increased bioavailability and metabolic adaptations, as well as adherence to intake of supplements, during normal pregnancy.…”
Section: Discussionsupporting
confidence: 87%